2010
DOI: 10.1111/j.1744-9987.2010.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Humoral Mediators and the Effect on the Survival of Septic Patients by Hemoperfusion With Neutral Microporous Resin Column

Abstract: The aim of this study is to evaluate the impact of neutral microporous resin hemoperfusion on hemodynamic improvement, removal of inflammatory cytokines, and mortality in critical care patients with severe sepsis. Forty-four patients with severe sepsis or septic shock were randomized to HA type hemoperfusion treatment (N=24) or standard therapy (N=20). Those undergoing hemoperfusion treatment received HA330 hemoperfusion. We measured the plasma concentrations of IL-6 and IL-8 at the start of every hemoperfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 16 publications
2
87
1
8
Order By: Relevance
“…To date, they have been thoroughly studied and widely used in China with no reported safety concerns [31-37]. Important to note that, apart from a few incidents of fever described by the studies of Huang et al [33] and Hu et al [35], no clinically significant side effects including symptoms and laboratory findings suggestive of bio-incompatibility were reported in these studies. Drop in platelet count was noted but was often transient, described as not clinically significant, and not resulting in bleeding events or requirement of blood transfusion.…”
Section: Discussionmentioning
confidence: 82%
“…To date, they have been thoroughly studied and widely used in China with no reported safety concerns [31-37]. Important to note that, apart from a few incidents of fever described by the studies of Huang et al [33] and Hu et al [35], no clinically significant side effects including symptoms and laboratory findings suggestive of bio-incompatibility were reported in these studies. Drop in platelet count was noted but was often transient, described as not clinically significant, and not resulting in bleeding events or requirement of blood transfusion.…”
Section: Discussionmentioning
confidence: 82%
“…A previous study carried out by our research group has demonstrated the biocompatibility, in terms of cytotoxicity, of the housing and the beads material [13]. HA cartridges are among the widely studied and used in China: several trials have been conducted and confirmed their reliability in clinical application [14][15][16], as reported in a recent review [12].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Hemsoperfuion using HA resin perfusion, a neutral macroporous resin adsorption 500-5 000 Da major molecular weight substance, can absorb a variety of proteins binding toxins and cytotoxic substances, which inhibit regeneration of liver. [10] CVVH can continually eliminate the molecular substances, ammonia and other toxic substances such as false neurotransmitters, free fatty acids, amino acids, aromatic thiols in patients with acute liver failure, increase the content of CAMP in cerebrospinal fluid, improve energy metabolism in the brain, alleviate and ameliorate hepatic encephalopathy. CVVH can accurately control capacity, continuously and slowly remove the solute and liquid, regulate water, electrolyte and acid-base balance, and reduce the occurrence of brain edema in patients with acute liver failure.…”
Section: Discussionmentioning
confidence: 99%